Respuesta :

Answer:

The functions are inverses; f(g(x)) = x ⇒ answer D

[tex]h^{-1}(x)=\sqrt{\frac{x+1}{3}}[/tex] ⇒ answer D

Step-by-step explanation:

* Lets explain how to find the inverse of a function

- Let f(x) = y

- Exchange x and y

- Solve to find the new y

- The new y = [tex]f^{-1}(x)[/tex]

* Lets use these steps to solve the problems

∵ [tex]f(x)=\sqrt{x-3}[/tex]

∵ f(x) = y

∴ [tex]y=\sqrt{x-3}[/tex]

- Exchange x and y

∴ [tex]x=\sqrt{y-3}[/tex]

- Square the two sides

∴ x² = y - 3

- Add 3 to both sides

∴ x² + 3 = y

- Change y by [tex]f^{-1}(x)[/tex]

∴ [tex]f^{-1}(x)=x^{2}+3[/tex]

∵ g(x) = x² + 3

∴ [tex]f^{-1}(x)=g(x)[/tex]

The functions are inverses to each other

* Now lets find f(g(x))

- To find f(g(x)) substitute x in f(x) by g(x)

∵ [tex]f(x)=\sqrt{x-3}[/tex]

∵ g(x) = x² + 3

∴ [tex]f(g(x))=\sqrt{(x^{2}+3)-3}=\sqrt{x^{2}+3-3}=\sqrt{x^{2}}=x[/tex]

f(g(x)) = x

The functions are inverses; f(g(x)) = x

* Lets find the inverse of h(x)

∵ h(x) = 3x² - 1 where x ≥ 0

- Let h(x) = y

∴ y = 3x² - 1

- Exchange x and y

∴ x = 3y² - 1

- Add 1 to both sides

∴ x + 1 = 3y²

- Divide both sides by 3

∴ [tex]\frac{x + 1}{3}=y^{2}[/tex]

- Take √ for both sides

∴ ± [tex]\sqrt{\frac{x+1}{3}}=y[/tex]

∵ x ≥ 0

∴ We will chose the positive value of the square root

∴ [tex]\sqrt{\frac{x+1}{3}}=y[/tex]

- replace y by [tex]h^{-1}(x)[/tex]

∴ [tex]h^{-1}(x)=\sqrt{\frac{x+1}{3}}[/tex]